The Influence of Brand Image and Brand Trust on Purchase Decision of Vivo Smartphones Among Undergraduate Students of The 2020 Cohort At STIMI Banjarmasin - Rahmat Arya, Khalid; Wahab, Abd; Alfiannor, Alfiannor (Hut Publication Business and Management, 2024)
This study aims to analyze the influence of Brand Image and Brand Trust on purchasing decisions at STIMI Banjarmasin campus. The research uses a quantitative method with a survey approach. Data was collected through a questionnaire distributed to 31 respondents, consisting of students who use Vivo smartphones. Data analysis was conducted using multiple linear regression methods. The purpose of this study is to examine the relationship between independent variables, namely Brand Image and Brand Trust, and the dependent variable, Purchase Decision. Data collection employed a Likert Scale questionnaire and purposive sampling method. Data analysis was performed using Multiple Linear Regression with the assistance of SPSS 27. The results show that Brand Image influences students’ Purchase Decision by 21.62%. Brand Trust has a significant influence of 29.80%. Furthermore, Brand Image and Brand Trust have a combined significant impact of 43.41%.